Bilateral ptosis: an atypical presentation of neurocysticercosis. (26th July 2012) - Naphade, Pravin Umakant; Singh, Maneesh Kumar; Garg, Ravindra Kumar; Rai, Dheeraj
Abstract : Isolated ptosis is a rare presentation of neurocysticercosis (NCC). Here we report the case of a 45-year-old woman who presented with acute onset bilateral symmetrical ptosis with no other neurological deficit. Her imaging revealed a single cystic ring-enhancing lesion with perilesional oedema in the midbrain suggestive of NCC. She responded well to prednisolone.